Hepatitis B virus and hepatitis C virus reactivation in cancer patients receiving novel anticancer therapies. (October 2022) - Mustafayev, Khalis; Torres, Harrys
Abstract: Background: Cancer patients with hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are at high risk of viral reactivation after cancer treatment. However, there is a paucity of data regarding HBV or HCV reactivation in cancer patients who receive newer anticancer drugs such as immune checkpoint inhibitors; Bruton tyrosine kinase (BTK) inhibitors; agents targeting CD22, CD38, and CC chemokine receptor 4 (CCR4); and chimeric antigen receptor (CAR) T-cell therapies. Objectives: In this narrative review article, we describe the rate, characteristics, and outcomes of HBV and HCV reactivation in patients receiving novel systemic anticancer therapies. Sources: We searched MEDLINE for all original research articles, case reports, and systematic reviews published in English between July 2013 and December 2021 on cancer patients with HBV or HCV infection receiving novel systemic anticancer therapy. Content: The risk of HBV or HCV reactivation is not well defined in cancer patients receiving immune checkpoint inhibitors (durvalumab, atezolizumab, nivolumab, pembrolizumab, ipilimumab, and tremelimumab); BTK inhibitors (ibrutinib and acalabrutinib); agents targeting CD22 (inotuzumab ozogamicin), CD38 (daratumumab, isatuximab), and CCR4 (mogamulizumab); and CAR T-cell therapy (axicabtagene-ciloleucel). However, screening for chronic HBV and HCV infections and routine monitoring of patients with such infections during novel anticancer therapy are recommended for early identification of viral reactivation, which can impact outcomes of oncologic treatment or be fatal. Implications: Specific strategies for risk assessment, monitoring, and management should be designed to reduce the risk of reactivation after novel anticancer therapy in patients with chronic HBV or HCV infections.